Literature Review: STEAM Approach to Improve High School Students' Problem-Solving Ability in Physics Learning - Vivian Oktab Fransiska; Dwikoranto; Nina Fajriyah Citra (Universitas Negeri Surabaya, 2025)
Objective: This study aims to collect information on the STEAM approach to enhance high school students' problem-solving skills in physics learning. Method: The method employed is a systematic literature review (SLR) using the PRISMA method. Article Collections or journals were searched using tools, namely Watase Uake, to assist in the search. Results: From as many as (245) relevant articles, researchers identify and filter so that researchers get the results of as many as (20) articles to be reviewed. Based on the literature review conducted, researchers found that learning using the STEAM learning approach can improve problem-solving skills. Novelty: The STEAM approach offers advantages over traditional methods, including an enhanced ability to identify problems, think critically, develop creative solutions, understand concepts, analyze information, increase motivation and interest, and improve student learning outcomes. These problem-solving skills are needed to be equipped to face various challenges in the coming era. A literature review indicates that learning with the STEAM approach can enhance problem-solving skills and hold promising potential, particularly in physics subjects at the high school grade XI level. The STEAM approach offers advantages over traditional methods, including an improved ability to identify problems, think critically, develop creative solutions, understand concepts, analyze information, increase motivation and interest, and enhance student learning outcomes.